Robot or radiation? A qualitative study of the decision support needs of men with localised prostate cancer choosing between robotic prostatectomy and radiotherapy treatment. Issue 7 (July 2019) - Smith, Allan 'Ben'; Rincones, Orlando; Sidhom, Mark; Mancuso, Pascal; Wong, Karen; Berry, Megan; Forstner, Dion; Bokey, Leslie; Girgis, Afaf
Highlights: Treatment choice is primarily influenced by clinicians' (mainly urologists') advice. Most patients preferred robotic prostatectomy before seeing a radiation oncologist. Patients valued seeing both a urologist and radiation oncologist. Patients need information about all treatments earlier in treatment decision-making. Abstract: Objective: To understand how best to support men diagnosed with localised prostate cancer to decide which treatment option best suits their needs, when robotic prostatectomy and radiotherapy are equally appropriate to offer them. Methods: Twenty-five men recently diagnosed with localised prostate cancer completed semi-structured interviews asking about information/decision-making needs before and/or after attending a combined clinic in which they consulted a urologist and a radiation oncologist regarding treatment options. Data was transcribed verbatim and thematically analysed. Results: Most men preferred robotic prostatectomy pre-combined clinic and chose it afterwards. The thematic analysis revealed four themes: 1) trust in clinicians and the information they provide is critical for treatment choice, 2) perceived fit between treatment characteristics and personal circumstances, 3) additional considerations: specific side effects, socio-emotional and financial factors, and 4) need for tailored information delivery. Robotic prostatectomy was mistakenly believed to provide a more definitive cure than radiotherapy, which was seen as having a lesser lifestyle impact. Conclusions: Treatment choice is largely dependent on clinicians' (mainly urologists') recommendations. Practice implications: Patients need more balanced information about alternatives to robotic prostatectomy earlier in the treatment decision-making process. Referral to a radiation oncologist or combined clinic shortly after diagnosis is recommended.